2001
DOI: 10.1021/jf0015221
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Triene Oxidation Products of α-Farnesene Induce Symptoms of Superficial Scald on Stored Apples

Abstract: The sesquiterpene alpha-farnesene (1) and its conjugated triene oxidation products accumulate in the skin of apples after harvest and are implicated as the causal agents of superficial scald. Conjugated triene oxidation products and analogues were synthesized and applied to the surface of Granny Smith apples either as vapors or in squalane. Farnesyl hydroperoxide (2a), trienol (2b), endoperoxide (3a), dehydronerolidol (5), and cumyl hydroperoxide (4) all produced the symptoms of superficial scald when applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 50 publications
3
67
0
1
Order By: Relevance
“…TC are generated as a product of the oxidation of AF during the storage of apples and have been identified as the direct cause of cellular damage that leads to the expression of scalding symptoms (Whitaker et al, 1997;Rowan et al, 2001). The application of 1-MCP to fruit with normal and step-wise cooling resulted in significantly lower levels of TC 258; 269 and 281 in comparison to fruit without treatment, throughout all the evaluations ( Figure 3A, 3B and 3C).…”
Section: Chemical Compounds and The Incidence Of Superficial Scaldmentioning
confidence: 96%
See 1 more Smart Citation
“…TC are generated as a product of the oxidation of AF during the storage of apples and have been identified as the direct cause of cellular damage that leads to the expression of scalding symptoms (Whitaker et al, 1997;Rowan et al, 2001). The application of 1-MCP to fruit with normal and step-wise cooling resulted in significantly lower levels of TC 258; 269 and 281 in comparison to fruit without treatment, throughout all the evaluations ( Figure 3A, 3B and 3C).…”
Section: Chemical Compounds and The Incidence Of Superficial Scaldmentioning
confidence: 96%
“…Given that this alteration is induced by the low-temperature storage, it is accepted as a manifestation of chilling injury (Watkins et al, 1995). It has been demonstrated that superficial scald is associated with oxidation of α-farnesene to conjugated trienes (Anet, 1972;Rowan et al, 2001;Arquiza et al, 2005;Isidoro and Almeida, 2006), which appear in greater concentrations, than just the accumulation of α-farnesene at the end of the storage period (Huelin and Coggiola, 1968;Meir and Bramlage, 1988;Whitaker et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Superficial scald usually appears during shelf life of fruits removed from cold storage, but with highly susceptible cultivars the scald can appear even during storage [1]. Scald has been associated with oxidation of α-farnesene and the consequent accumulation of conjugated trienes [2].…”
Section: Introductionmentioning
confidence: 99%
“…Golden Delicious associated with a mouldy, musty and earthy off-odour in this research were two endoperoxides with molecular weights 236 and 252, respectively, as described previously (Rowan et al 1995(Rowan et al , 2001. These compounds were eluted after 27.5 and 30.5 min and encompassed 0.5% and 0.7% of the peak area, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…α-Farnesene autooxidises easily at 1°C to 2,6, 10-trimethyldodeca-2,7(E),9(E),11-tetraen-6-ol, 6-hydroperoxy-2,6,10-trimethyldodeca-2,7(E),9(E)-11-tetraene, its 7E,9Z isomers and 6-methyl-5-hepten-2-one (Anet 1969; Rowan et al 1995Rowan et al , 2001). On this basis it was concluded that the mouldy, musty and earthy off-odour of cv.…”
mentioning
confidence: 99%